Re-engaging with Primary Mathematics Through Sustained Professional Development: A Case Study - Catherine Attard (Southeast Asian Mathematics Education Journal, 2017)
This paper reports on aspects of a case study of sustained professional development to improve teacher and student engagement with mathematics. Teachers from Grades 3 to 6 in one Western Sydney primary school were involved with a professional development program over the course of 18 months. Prior to this, the teachers limited opportunities to engage with any mathematics-related professional development. The professional development program resulted in improved teacher engagement and the development of a community of practice within the school. Findings from the study align with recommendations from literature that teachers must be provided with opportunities for continuing professional development that is self-nominated and focused on individual needs as well as group needs.